Desenvolvimento e avaliação de programa de educação permanente para técnicos em enfermagem em Unidade de Terapia Intensiva cardiopediátrica - Borim, Bruna Cury (2015)
The Nursing profession has been facing continuous transformations demonstrating the importance of professional continuing education to extend knowledge following the technological development without impairing quality of care. Nursing assistants and technicians account for nearly 80% of the current Nursing professionals in Brazil and are responsible for direct and uninterrupted patient care. There is a need for knowledge improvement of these professionals to achieve excellence in Nursing care. Objective: To develop and evaluate a continuing education program for Nursing technicians in pediatric cardiac intensive care unit based on a virtual learning environment entitled EDUCATE. Methods: From July to September 2015, twenty-four Nursing technicians working at the pediatric cardiac ICU at Hospital da Criança e Maternidade from São José do Rio Preto, SP participated fully in the continuing education program called EDUCATE developed in a virtual environment learning using Wix® platform, allowing access to video classes and pre and post-training theoretical evaluation questionnaires outside the work environment. The evaluation tools recorded their knowledge evolution, technological difficulties, didactic and overall rating. Results: Knowledge development, descriptively presented, was positive at more than 66.7%. Content and training were considered "excellent" for the majority of participants and 90% showed interest in utilizing technological resources. Technical difficulties were encountered by 40% of participants which included problems with internet access, log-in and lack of technical expertise (5%). Conclusion: The continuing education program evaluation based on a virtual learning environment (EDUCATE) showed to be effective and able to contribute in theoretical knowledge improvement for Nursing technicians in pediatric cardiac intensive care unit.